Effect of ethanol extract of Calceolaria myriophylla “zapatilla” on the model of metabolic syndrome fructosa induced in rats - Condorhuamán, Martín (2014)
This study aimed to determine the effect of ethanol extract of Calceolaria myriophylla "shoe" in the metabolic syndrome induced by fructose in rats. Was made qualitative phytochemical analysis and used 48 male albino rats of race Holtzmann 2 months old with a weight fluctuated between 180 and 200 g, was performed induction of metabolic syndrome in rats by oral administration of fructose to 60% for 90 days and work according to the following design: six groups of eight animals each group divided into control group, fructose group, fructose group more ethanolic extract (03 groups at doses of 200, 400 and 600 mg/kg, respectively and fructose more drugs (atorvastatin 20 mg/kg group and 20 mg captopril mg/kg in combination), treatments were administered orally for 90 days. Were observed decreased levels glucose, lipid profile (total cholesterol, HDL-cholesterol and triglycerides), systolic and diastolic blood pressure and body weight of rats in the treated groups. Was concluded that the ethanol extract showed effect on clinical and biochemical criteria on metabolic syndrome fructose induced in rats are statistically significant (p<0,05) and the presence of abundant amounts of flavonoids and phenolic compounds.